MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUI TEKNIK GROUP SEQUENCING (GS) BAGI ANAK TUNARUNGU - Doni - Candra (Jurnal Penelitian Pendidikan Khusus, 2013)
This research was backgrounded from the observation that researcher did at SDLB Negeri 36 Muaro Sijunjung. For deaf children at class D.VI that have problem at reading comprehension. Based on explanation before this research have purpose to improve reading comprehension ability by using group sequencing technique at material reading comprehension that include in the curriculum. This research is using quasy experimencal approach with from single subject research (SSR) by design A-B. Kind of behavior percentage child ability in reading comprehension by answer the questions rightly for five questions at students’ work sheet that relative time same are 60 minute. The technique for analysis the data that used a form of Visual Analysis of Grafik. The result of this research was analyzed that include sum up at Baseline condition for five time of meeting and Treatment condition for sevent time of meeting. The result of this research show that hypothesis (Ha) accept, it means that reading comprehension ability deaf children (x) was improving through application group sequencing technique. So as suggested to school side and teacher to become the result of this researcher as reference to develop the study reading comprehension ability in this school.